Pityriasis rosea among pediatric patients: a cross-sectional, institution based study - Mondal, Avijit (Journal of Pakistan Association of Dermatologists, 2022)
Background: Pityriasis rosea (PR) is an acute, self-limited papulosquamous disorder. The incidence of PR is around 0.5–2% and is commonly seen in young healthy persons, between 10 to 35 years. In pediatric age, prevalence is between 8% to 12% below 10 years and 4% below 4 years. The common differential diagnosis of PR are syphilis, tinea corporis, pityriasis versicolor, guttate psoriasis and pityriasis lichenoides. Aims: The aim of this study was to find out the demographic and clinical profiles of pityriasis rosea among paediatric (less than 18 years) patients. Patients and methods: The study was carried out over a period of twelve months at Dermatology Out-patient department at a tertiary care centres of East India and a total of fifty paediatric (less than 18 years) cases of PR were recruited for the study. The diagnosis was made clinically with the details of history, examination and relevant investigations being recorded in case record form, after getting consent from patient or guardian. Results: Fifty pityriasis rosea (PR) patients in pediatric age group were recruited from Dermatology out-patient department during study period. The mean age of presentation was 12.45 years with range being 2 to 18 years. Females outnumbered males (Female: Male ratio 1.27:1) in our study. Classical herald patch was seen in 42 (84%) cases. Atypical morphology was seen in 12 (24%) cases. Pruritus was the only symptom which was noted in 31 patients (62%). Conclusion: PR is usually diagnosed clinically but atypical presentation of PR is not uncommon. So high degree of clinical suspicion is needed to diagnosis the atypical form. Key words: pityriasis rosea, pediatric pityriasis rosea, atypical presentation